2019
DOI: 10.1002/ajb2.1356
|View full text |Cite
|
Sign up to set email alerts
|

Linking coordinated hydraulic traits to drought and recovery responses in a tropical montane cloud forest

Abstract: PREMISE:Understanding plant hydraulic functioning and water balance during drought has become key in predicting species survival and recovery. However, there are few insightful studies that couple physiological and morphological attributes for many ecosystems, such as the vulnerable Tropical Montane Cloud Forests (TMCF). In this study, we evaluated drought resistance and recovery for saplings for five tree species spanning deciduous to evergreen habits from a Mexican TMCF. METHODS:In drought simulations, water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
2
7
0
1
Order By: Relevance
“…Functional traits have been used as an approach to evaluate plant species performance in different light conditions (Poorter and Bongers, 2006;Saldaña-Acosta et al, 2009;Toledo-Aceves et al, 2017), water availability levels (Amissah et al, 2015) and soil conditions (Vergara-Gómez et al, 2020). Leaf functional traits of each studied species responded accordingly to the functional group they belong in a continuum of light requirements (Poorter and Bongers, 2006), where trees may have different leaf traits responses depending on water availability (Poorter and Markesteijn, 2008;Berry et al, 2019). Trade-offs have been widely reported, but some studies have found that traits and survival of tropical forest tree seedlings respond independently to drought and shade (Amissah et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Functional traits have been used as an approach to evaluate plant species performance in different light conditions (Poorter and Bongers, 2006;Saldaña-Acosta et al, 2009;Toledo-Aceves et al, 2017), water availability levels (Amissah et al, 2015) and soil conditions (Vergara-Gómez et al, 2020). Leaf functional traits of each studied species responded accordingly to the functional group they belong in a continuum of light requirements (Poorter and Bongers, 2006), where trees may have different leaf traits responses depending on water availability (Poorter and Markesteijn, 2008;Berry et al, 2019). Trade-offs have been widely reported, but some studies have found that traits and survival of tropical forest tree seedlings respond independently to drought and shade (Amissah et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Droughts induced by climate change will affect the performance of trees globally, but the direction (positive or negative) and magnitude of these effects will depend on the intensity of droughts and the tolerance of species to water shortage conditions (Allen et al, 2015). Considering that climate change may affect plants differently, increasing number of studies have focused on the responses of tree species and ecosystems to drought stress (Beier et al, 2012;Berry et al, 2019). The climate change responses of tree species have motivated studies on functional traits and there is growing interest in analyzing how these traits vary with increasing drought (Badano et al, 2018(Badano et al, , 2019Berry et al, 2019;Williams-Linera et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations